As forças de paz ou a paz à força: etnografia de uma missão de paz da ONU no Haiti - Santiago, Ana Elisa (Universidade Federal de São Carlos, 2022)
Over the past century Haiti has experienced successive international interventions in the name of peace. By alleging that Haiti’s internal instability threatens international security, the United Nations (UN) has undertaken peace operations in the country and installed administrative apparatuses to guarantee the proper functioning of democratic institutions, assessed by institutionally established criteria. This ethnographic analysis of one of the peace operations in Haiti – MINUSTAH – explores how the data production on the levels of violence builds an intervention-legitimizing consensus that mobilizes an international bureaucratic apparatus, whose role is to produce even more data in order to create what I call a “statecrafted landscape”. I carried out the field research among the documents, among the bureaucrats, among the Haitian social movements, and among the Brazilian military that participated in the mission. Empirical evidence from fieldwork among UN experts and Haitian activists suggest a mismatch between the Haiti inscribed in UN documents and the Haiti reiterated in local stories about the nation. By contrasting the production of ‘official history’ as a truth and ‘unofficial’ Haitian narratives, I will shed light on the relations of power involved in the enactment of historical facts. Field work among the military highlighted the relevance of the Brazilian Army's participation in MINUSTAH. Through combat experience acquired in Haiti, as well as the bureaucratic training required by the mission, the Armed Forces have improved their techniques for managing the territory and people, and have then reiterated their position as guardians of stability - at home and abroad - by manipulating legal resources to gain control over the population, engendering effects on internal politics and escalating a conservative and authoritarian power in Brazil.
Peacekeeping or keeping peace by force: Ethnography of a UN peacekeeping operation in Haiti
Keywords: ONU; Haiti; Cooperação internacional; Revolução; Operação de Paz; UN; Haiti; International cooperation; Revolution; Peacekeeping operation; CIENCIAS HUMANAS::ANTROPOLOGIA